The use of Edmodo in teaching writing in a blended learning setting - Purnawarman, Pupung; Susilawati, Susilawati; Sundayana, Wachyu (Universitas Pendidikan Indonesia, 2016)
The advancement of technology provides education with varioussolutions to create new learning environments. Edmodo as a learning platform is believed to offera solution in the teaching of English, particularly for teaching writing. This research was aimed to investigate how Edmodo as a learning platform,in a blended learning setting, was implemented in teaching writing in its combination with Genre-based Approach, how Edmodo facilitated students’ engagement, and how students perceived the use of Edmodo in teaching and learning activities. This research employed a qualitative approach with case study design. The research involved 17 participants from the eleventh grade of a senior high school in Bandung, Indonesia. The data were collected through observations, document analysis, interviews, and questionnaires. The results showed that in teaching writing,it was possible to integrate Edmodo into GBA writing cycles. Edmodo also facilitated students’ engagement cognitively during classroom sessions. The students showed various responses towards the use of Edmodo based on the Uses and Gratification Theory (UGT) framework. Some issues on the use of Edmodo identified in this research were bandwidth, confusion in using Edmodo, incompatibility of smartphone applications, and students’ lack responsibilities for learning. The suggestions for the authority and areas of further research are presented.